2016
DOI: 10.3892/mco.2016.983
|View full text |Cite
|
Sign up to set email alerts
|

Polaprezinc protects normal intestinal epithelium against exposure to ionizing radiation in mice

Abstract: Polaprezinc (PZ), an antiulcer drug, has been reported to have antioxidant effects. The purpose of the present study was to assess the radioprotective effects of PZ in the normal intestine of C57BL/6J mice. PZ was orally administered at 100 mg/kg body weight in the drinking water. Firstly, the present study compared the survival of normal intestinal crypt epithelial cells with mice that received PZ prior to or following irradiation. Next, the present study examined the sequential changes of the incidence of ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Endoscopic and histological analyses demonstrated that mucosal inflammation is significantly reduced in theses rats compared with control group (44). Another study also reported that administration of 100 mg/kg polaprezinc 2 h before experiment can reduce the apoptosis of intestinal epithelial cells in the duodenum, jejunum and ileum during ion beam injury, protecting the normal epithelial cells in the intestine (45).…”
Section: Radioactive Esophagitis Hayashi Et Almentioning
confidence: 84%
“…Endoscopic and histological analyses demonstrated that mucosal inflammation is significantly reduced in theses rats compared with control group (44). Another study also reported that administration of 100 mg/kg polaprezinc 2 h before experiment can reduce the apoptosis of intestinal epithelial cells in the duodenum, jejunum and ileum during ion beam injury, protecting the normal epithelial cells in the intestine (45).…”
Section: Radioactive Esophagitis Hayashi Et Almentioning
confidence: 84%
“…Hepilor R has been used for the treatment of peptic ulcers in Japan since 1994, and many studies tested it in the gastrooesophageal and intestinal areas (4-11). In the anorectal field, this compound has proven to be very effective in treating radiation proctitis (12,13) and ulcerative colitis, where it induced a significant clinical and endoscopic remission (14). Zinc-L-Carnosine induces mucosal repair, stimulating mucus production, antioxidant activity, and membrane-stabilising activity.…”
Section: Discussionmentioning
confidence: 99%
“…This compound proved to be very effective in treating radiation proctitis, a difficult clinical condition, significantly improving endoscopic pictures and symptoms (12,13). Furthermore, the product has been effectively tested in ulcerative colitis, where it induced a significant clinical and endoscopic remission (14).…”
Section: Introductionmentioning
confidence: 99%
“…A research dealing with the long‐term use of low‐dose aspirin found that the aggregate median of small intestinal swelling, erosion and ulcer lesions was considerably decreased in Polaprezinc group . Animal studies have revealed that oral Polaprezinc prior to radiotherapy can effectively reduce the apoptosis of jejunal crypt cells in rats . According to the drug specification of Polaprezinc in the treatment of gastric ulcer, the recommended oral dosage amounts to be 75 mg, two times daily, and the instruction clearly suggests that the dose may be increased in accordance with the disease status as well as severity of symptoms.…”
Section: Discussionmentioning
confidence: 99%